DIAMOND CRYSTALLIZATION IN FLUID AND CARBONATE-FLUID SYSTEMS UNDER MANTLE P-T CONDITIONS: 1. FLUID COMPOSITION - Sokol A.G.; Pal'yanov Yu.N.; Pal'yanova G.A.; Tomilenko A.A. (My University, 2004)
Graphite and a fluid-generating substance (silver oxalate, oxalic acid, or anthracene) were sealed in a platinum or a gold capsule and run for a long time at elevated pressure (5.7 GPa) and temperature (1200 or 1420°C). Both the starting materials and gases released from the capsule after the experiment were analyzed by gas chromatography. The results of the thermodynamic modeling of C-O-H fluid at 5.7 GPa and 1200-1500°C and at 7 GPa and 1300-1900°C were evaluated. The composition of the fluid generated by the decomposition of real substances was calculated. The experimental and calculated data show that the composition of CO2 and H2O-CO2 fluids changed considerably during the long-term diamond crystallization experiments in the C-O-H system. The compositions of water and methane-hydrogen fluids are more stable. The compositional changes of the H2O-CO2 and H2O fluids with increasing temperature from 1200 to 1420°C indicate a decrease in hydrogen fugacity in the material of the high-pressure cell surrounding the experimental capsules.